STRUKTUR KOMUNITAS IKAN DAN TERUMBU KARANG PULAU TUNDA, KABUPATEN SERANG, BANTEN - Aurel Satyaning Ati; Muhammad Ariq Rafii Ramadhan; Muhammad Adil Awal; Rossa Rechtisia (LPPM Universitas Negeri Jakarta, 2022)
Tunda Island is one of the leading marine destinations in Banten Province which has high potential biodiversity. This study aimed to determine the health condition of the Tunda Island coral reef ecosystem. The method used in this study was Line Intercept Transect (LIT) method for coral reef and Belt Transect method for reef fish. Based on coral reef survey, the percentage of coral coverage on Tunda Island was 34.7%. From this value the coral reefs of Tunda Island were included in the sufficient category. The results of a survey of fish showed that there were 57 species from 17 families, which is dominated from Pomacentridae. The diversity index value (H ') of reef fish was 3.143, which showed that the diversity of reef fish around Tunda Island was high, and the uniformity index value (e) was 0.777, which showed that in Tunda Island waters the spread of fish species was stable.